METHOD DEVELOPMENT OF APPLYING SHRINKAGE VALUES INTO BASE PATTERN OF MEN'S GARMENT DYED SHIRT - Sidikjanov, Jafar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
One of the major challenges faced when designing garments in garment dyeing is the significant shrinkage of cotton fabric in both length and width during the dyeing process. In previous researches, shrinkage values ​​of various cotton fabrics were determined, drawing a base pattern for designing a men's shirt produced by garment dyeing, and a method of calculating the shrinkage values ​​of the selected cotton fabric was researched, and in this article, the scheme defining main feature points on Cartesian coordinate system and drawing of the shirt new pattern based on shrinking values was developed​.